Genetic Testing When There is a Mix of Compulsory and Voluntary Health Insurance - Michael Hoel; Tor Iversen (Center for Economic Studies and ifo Institute (CESifo), 2001)
Genetic insurance can deal with the negative effects of genetic testing on insurance coverage and income distribution when the insurer has access to information about test status. Hence, efficient testing is promoted. When information about prevention and test status is private, two types of social inefficiencies may occur; genetic testing may not be done when it is socially efficient and genetic testing may be done although it is socially inefficient. The first type of inefficiency is shown to be likely for consumers with compulsory insurance only, while the second type of inefficiency is more likely for those who have supplemented the compulsory insurance with substantial voluntary insurance. This second type of inefficiency is more important the less effective prevention is. It is therefore a puzzle that many countries have imposed strict regulation on the genetic information insurers have access to. A reason may be that genetic insurance is not yet a political issue, and the advantage of shared genetic information is therefore not transparent.
Keywords: 330; Genetic testing insurance; private information; compulsory/voluntary mix